Diseminasi Rumah Tumbuh Tanaman Hidroponik sebagai Upaya Optimalisasi Tumbuh Kembang Tanaman di Kota Palangka Raya (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2020)
The total population of Palangka Raya city in 2017 reached 258,550 people, with such a population, the need for food, especially vegetables, is very much needed. Healthy vegetables without preservatives and pesticides are currently very popular in the city of Palangka Raya, therefore it is necessary to increase the production capacity of hydroponic vegetables in order to meet market needs for vegetables and learning laboratory facilities for the community and students in particular. Hydroponic plants are very possible to be cultivated in a small area using the right construction. The results of an interview with one of the hydroponic plant farmer groups 'Anak Pangaringan', Mr. Gamaliel Tumon, ST, who has a yard with a size of 3 x 16 m. With simple wooden construction, they have succeeded in growing lettuce, pakcoy, red spinach and water spinach with a harvest period of one month, have marketed their crops to restaurants, supermarkets in the city of Palangka Raya and those who come to buy retail. adequate hydroponic plant growing house construction. So that a hydroponic plant growing house construction is designed that can help hydroponic owners to be able to manage the best nutrition, so that the growing house is ideal in terms of lighting, air circulation and plant water systems so that plants can increase food production optimally for their own needs and for increase income. The end result of designing this system is to produce optimal water conditions according to the type of plant selected by the user because water always flows smoothly, and by using an inseknet it can control pests / insects and plants still get fresh air.